Sur une stratégie de calcul multiéchelle pour l’analyse des structures composites: Discrétisation et performances - Loiseau, Olivier; Ladevèze, Pierre; Dureisseix, David (European Journal of Computational Mechanics, 2002)
In order to solve efficiently large scale problems arising from the simulation of heterogeneous structures, described up to the microscale, a multiscale computational strategy strongly related to homogenization techniques has been proposed in [LAD 00]. In this paper, specific tools required to address the case of composite materials are proposed: the use of a third scale and of the periodic media homogenization theory within the areas located far from the boundaries.